Nematicidal activities of natural lignans and derivatives from milky thistle against Meloidogyne incognita - Pandey, Rakesh (Indian Phytopathology, 2011)
The nematicidal activity of varying concentrations of lignans and the various derivatives obtained from Silybum marianum was evaluated against root knot nematode Meloidogyne incognita (Kofoid and White) Chitwood. The percentage mortality and inhibition of hatching of M. incognita were found to be directly proportional to the concentration of compounds and derivatives on prolonged exposure. Overall, silybin pentabenzoate exhibited the highest nematicidal activity causing 99% mortality at 500 Âµg/ ml after 24 hours of exposure. The results obtained are the first experimental confirmation of nematicidal activity of these compounds, thereby might prove a boon for further development and understanding of plant derived nematicides.